Evaluation of the impact vocational high school center of excellence program on hospitality skills - Dwi Ratnasari; Edy Supriyadi; Fitri Alfarisa (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2025)
The Center of Excellence Vocational High School Program aims to strengthen vocational education through a work-based learning approach aligned with industry needs. However, empirical evidence regarding its impact on students’ technical competencies remains limited. This study analyzes the impact of the program on hospitality students at SMK Negeri 1 Sijuk using the CIPP evaluation model, focusing on the Input and Product components. Data were collected through interviews and questionnaires from 30 respondents, including the principal, vocational teachers, an industry representative, and students. Instrument validity was assessed using Aiken’s V, and reliability was estimated with Cronbach’s Alpha. The findings indicate that the program has achieved strong institutional readiness, with most Input indicators categorized as Very Good. The Product component also showed high satisfaction, particularly in graduate quality and competency certification, suggesting that graduates possess adequate hard and soft skills. However, implementation gaps were identified, particularly in teacher readiness, mindset transformation, and the suboptimal application of Project-Based Learning (PjBL). Industry feedback further highlighted concerns regarding students’ readiness before internships. Overall, the main challenge lies in strengthening instructional implementation and enhancing student preparedness prior to workplace training.